Pengaruh Kualitas Jasa terhadap Keputusan Pembelian Speedy oleh Pengusaha Warnet di Kecamatan Telanaipura Jambi - Eva Setia Rini Damanik (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
This study purposed to investigate the influence of service quality on purchasing decisions by employer speedy Telanaipura internet cafe in the district of Jambi. Samples in this study in the set with a survey method. Internet Cafe so set 30 as the study sample. The value of adjusted R Square is equal to 0.338 or 33.8%. This shows that the independent variables explained the dependent variable of 33.8% while the remaining 66.2% is explained by other variables not included in the model. F test showed that variables simultaneously technical, functional and corporate image significantly influence purchasing decisions. While the t test results showed that the variable corporate image significantly influence purchasing decisions, while technical and functional variables partially no significant effect on the capital structure.